A rapid review of consumer health information needs and preferences - Ramsey, Imogen; Corsini, Nadia; Peters, Micah D.J.; Eckert, Marion (Patient education and counseling, 2017)
•Consumers access healthcare information through an array of platforms and for varying purposes.•The internet is used for health information health-related decision making.•Health professionals remain a preferred source of healthcare for many consumers.•There may be inequitable information access for disadvantaged consumer groups.•Research should investigate how preferences vary by disease and stage of illness. This rapid review summarizes best available evidence on consumers’ needs and preferences for information about healthcare, with a focus on the Australian context. Three questions are addressed: 1) Where do consumers find and what platform do they use to access information about healthcare? 2) How do consumers use the healthcare information that they find? 3) About which topics or subjects do consumers need healthcare information? A hierarchical approach was adopted with evidence first sought from reviews then high quality studies using Medline (via PubMed), CINAHL, Embase, the JBI Database of Systematic Reviews and Implementation Reports, the Campbell Collaboration Library of Systematic Reviews, EPPI-Centre, and Epistemonikos. Twenty-eight articles were included; four systematic reviews, three literature reviews, thirteen quantitative studies, six qualitative studies, and two mixed methods studies. Consumers seek health information at varying times along the healthcare journey and through various modes of delivery. Complacency with historical health information modes is no longer appropriate and flexibility is essential to suit growing consumer demands. Health information should be readily available in different formats and not exclusive to any single medium.